Rekonstruksi Filosofis Dan Yuridis CSR Bagi Pembangunan Berkelanjutan Di Indonesia - Defril Hidayat (El-Dusturie, 2026)
Abstract: This study analyzes the disharmony in the regulation of Corporate Social Responsibility (CSR) within Indonesia’s legal system and its implications for legal certainty and social justice. This research is a normative legal study employing a statutory approach, a conceptual approach, and a philosophical approach. Legal materials are analyzed using a qualitative-prescriptive method through grammatical, systematic, and teleological legal interpretation of CSR provisions in the Limited Liability Company Law, the Investment Law, and the Environmental Protection and Management Law. The findings indicate that CSR regulation in Indonesia remains sectoral, fragmented, and poorly integrated, as reflected in divergent definitions, inconsistencies in the scope of legal subjects, and weak enforcement mechanisms and sanctions. This condition generates legal uncertainty and undermines the effectiveness of CSR as an instrument for sustainable development. The novelty of this study lies in the philosophical and juridical reconstruction of CSR within the framework of legal development, positioning CSR not merely as an administrative obligation of corporations, but as a legal instrument for realizing social justice based on the values of Pancasila and Article 33 of the 1945 Constitution of the Republic of Indonesia. This study provides a scholarly contribution by proposing a harmonization model of CSR regulation through the enactment of a standalone, comprehensive, and integrative CSR Law as a national legal framework. Such regulation is expected to unify principles, legal subjects, implementation mechanisms, reporting, and supervision of CSR, thereby enabling CSR to function optimally as a legal instrument for sustainable development and equitable social welfare.  Keywords: Corporate Social Responsibility; legal harmonization; social justice; sustainable development; legal certainty.   Abstrak: Penelitian ini menganalisis disharmoni pengaturan Corporate Social Responsibility (CSR) dalam sistem hukum Indonesia serta implikasinya terhadap kepastian hukum dan keadilan sosial. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan peraturan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan filosofis. Bahan hukum dianalisis melalui teknik analisis kualitatif-preskriptif, dengan menggunakan penafsiran gramatikal, sistematis, dan teleologis terhadap ketentuan CSR dalam Undang-Undang Perseroan Terbatas, Undang-Undang Penanaman Modal, dan Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup. Hasil penelitian menunjukkan bahwa pengaturan CSR di Indonesia masih bersifat sektoral, parsial, dan tidak sinkron, yang tercermin dari perbedaan definisi, ruang lingkup subjek hukum, serta ketiadaan mekanisme pengawasan dan sanksi yang tegas. Kondisi ini menimbulkan ketidakpastian hukum dan melemahkan efektivitas CSR sebagai instrumen pembangunan berkelanjutan. Kebaruan penelitian ini terletak pada rekonstruksi filosofis dan yuridis CSR dalam kerangka hukum pembangunan, yang menempatkan CSR tidak hanya sebagai kewajiban administratif korporasi, tetapi sebagai instrumen hukum untuk mewujudkan keadilan sosial berdasarkan nilai Pancasila dan Pasal 33 UUD NRI Tahun 1945. Penelitian ini berkontribusi secara ilmiah dengan menawarkan model harmonisasi regulasi CSR melalui pembentukan Undang-Undang CSR yang berdiri sendiri, komprehensif, dan integratif. Undang-undang tersebut diharapkan mampu menyatukan prinsip, subjek, mekanisme pelaksanaan, pelaporan, serta pengawasan CSR secara nasional, sehingga CSR dapat berfungsi secara optimal sebagai instrumen hukum bagi pembangunan berkelanjutan dan pemerataan kesejahteraan masyarakat.   Keywords: Corporate Social Responsibility; harmonisasi hukum; keadilan sosial; pembangunan berkelanjutan; kepastian hukum. Abstract: This study analyzes the disharmony in the regulation of Corporate Social Responsibility (CSR) within Indonesia’s legal system and its implications for legal certainty and social justice. This research is a normative legal study employing a statutory approach, a conceptual approach, and a philosophical approach. Legal materials are analyzed using a qualitative-prescriptive method through grammatical, systematic, and teleological legal interpretation of CSR provisions in the Limited Liability Company Law, the Investment Law, and the Environmental Protection and Management Law. The findings indicate that CSR regulation in Indonesia remains sectoral, fragmented, and poorly integrated, as reflected in divergent definitions, inconsistencies in the scope of legal subjects, and weak enforcement mechanisms and sanctions. This condition generates legal uncertainty and undermines the effectiveness of CSR as an instrument for sustainable development. The novelty of this study lies in the philosophical and juridical reconstruction of CSR within the framework of legal development, positioning CSR not merely as an administrative obligation of corporations, but as a legal instrument for realizing social justice based on the values of Pancasila and Article 33 of the 1945 Constitution of the Republic of Indonesia. This study provides a scholarly contribution by proposing a harmonization model of CSR regulation through the enactment of a standalone, comprehensive, and integrative CSR Law as a national legal framework. Such regulation is expected to unify principles, legal subjects, implementation mechanisms, reporting, and supervision of CSR, thereby enabling CSR to function optimally as a legal instrument for sustainable development and equitable social welfare. Keywords: Corporate Social Responsibility; legal harmonization; social justice; sustainable development; legal certainty. Abstrak: Penelitian ini menganalisis disharmoni pengaturan Corporate Social Responsibility (CSR) dalam sistem hukum Indonesia serta implikasinya terhadap kepastian hukum dan keadilan sosial. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan peraturan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan filosofis. Bahan hukum dianalisis melalui teknik analisis kualitatif-preskriptif, dengan menggunakan penafsiran gramatikal, sistematis, dan teleologis terhadap ketentuan CSR dalam Undang-Undang Perseroan Terbatas, Undang-Undang Penanaman Modal, dan Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup. Hasil penelitian menunjukkan bahwa pengaturan CSR di Indonesia masih bersifat sektoral, parsial, dan tidak sinkron, yang tercermin dari perbedaan definisi, ruang lingkup subjek hukum, serta ketiadaan mekanisme pengawasan dan sanksi yang tegas. Kondisi ini menimbulkan ketidakpastian hukum dan melemahkan efektivitas CSR sebagai instrumen pembangunan berkelanjutan. Kebaruan penelitian ini terletak pada rekonstruksi filosofis dan yuridis CSR dalam kerangka hukum pembangunan, yang menempatkan CSR tidak hanya sebagai kewajiban administratif korporasi, tetapi sebagai instrumen hukum untuk mewujudkan keadilan sosial berdasarkan nilai Pancasila dan Pasal 33 UUD NRI Tahun 1945. Penelitian ini berkontribusi secara ilmiah dengan menawarkan model harmonisasi regulasi CSR melalui pembentukan Undang-Undang CSR yang berdiri sendiri, komprehensif, dan integratif. Undang-undang tersebut diharapkan mampu menyatukan prinsip, subjek, mekanisme pelaksanaan, pelaporan, serta pengawasan CSR secara nasional, sehingga CSR dapat berfungsi secara optimal sebagai instrumen hukum bagi pembangunan berkelanjutan dan pemerataan kesejahteraan masyarakat. Keywords: Corporate Social Responsibility; harmonisasi hukum; keadilan sosial; pembangunan berkelanjutan; kepastian hukum.